Modal Sosial dalam Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat Berkelanjutan - Munawaroh, Munawaroh; Suyanto, Edy; Masrukin, Masrukin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
Water as the main necessity of life should be fulfilled in quantity, quality, affordability, and continuously. However, there are many people still do not get proper clean water, especially in rural and suburban areas. The PAMSIMAS program is one of the mainstay programs of the Government that provides clean water and sanitation for rural and suburban communities through a community-based approach. The strength of developing drinking water and rural sanitation is very dependent on the social capital of community and local government. The PAMSIMAS program provides great support to encourage the realization of the sustainability of the water supply and sanitation system so that the community and village government can be focus in the PAMSIMAS approach in their village policies and to be able to maintain the sustainability of the PAMSIMAS program management.